(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cricket is a bat and ball game played between two teams of eleven players. Measuring individual performance of players is very essential for teams to win games. In 2008, BCCI announced the launch of a franchise based Twenty20 cricket tournament called Indian Premier League, one of the biggest sporting events of the world now, which helped Indian domestic cricket players to gain vast exposure at an international level. Performance analysis of cricket players is always a vital task for the team selection therefore, the principal purpose of this paper is to rank the players based on their performance and to find the key players in each season of IPL from 2008 to 2013 using principal component analysis. Quantifying individual player’s contribution is an important task in all team sports. There are several indicators available to measure player’s performance, which are based on different aspects of their contributions to the team, unfortunately these indicators are mostly related to each other in a manner that causes difficulty in constructing an overall performance measure but Principal component analysis (PCA) uses an orthogonal transformation to convert a set of observations of possibly correlated variables into a set of values of linearly uncorrelated variables to rank the players based on overall performance of each player.